THE WOMAN THAT MAKES AN IMPRESSION ON TURKISH PUBLIC RELATIONS HISTORY: BETÜL MARDIN - KAZANCI, Pakize (Journal of Management and Organization History, 2023)
The characteristics of practitioners performing the profession are as important as the Public Relations profession itself. As a free-spirited woman with a character who thinks and acts far beyond her age, Betûl Mardin is a successful communicator who has established an understanding of public relations in our country and played a major role in the perception of her as a professional. In this study, inferences have been made about the qualities that should come to the fore in practitioners, based on the characteristics that lead Betûl Mardin, who has achieved great success and was deemed worthy of considerable appreciation and awards in the sector, and her public relations understanding. The public relations specialist has a high persuasive ability and confidence, is serious, takes his job seriously, is hardworking, self-developing, reads a lot, has a high general culture, has rules, has ethical rules and is aware of the importance of these rules, has strong human relations, is more persuasive than other persuasion methods. The successful implementer must be socially responsible. Due to the structuring of the reputation, the work can be seen as a kind of architecture and patience should be used in the construction of the reputation